Answer:
(1, 2 )
Step-by-step explanation:
Given the 2 equations
y = - 3x + 5 → (1)
y = 4x - 2 → (2)
Substitute y = 4x - 2 into (1)
4x - 2 = - 3x + 5 ( add 3x to both sides )
7x - 2 = 5 ( add 2 to both sides )
7x = 7 ( divide both sides by 7 )
x = 1
Substitute x = 1 into (2) for corresponding value of y
y = (4 × 1) - 2 = 4 - 2 = 2
Solution is (1, 2 )
Hey !!
Check the attachment.
Hence, On proper calculations ,
We get our answer as D) 713.5 m^2
Hope it helps you :)
Answer:
910 bees
Step-by-step explanation:
There are 35 bees in a hive and we have 26 hives.
Take the number of hives and multiply by the number of bees per hive
26*35 =910
There are 910 bees total
Answer:
It is B
Step-by-step explanation: n is -1.5 and m is 2.5
-1.5 + 2.5 = 2
Answer: $12.65
Step-by-step explanation: sikeeeeeeeeeeee